Merancang "Materials of Writing Analytical Exposition Text (MOWAET)" untuk Pengajaran Bahasa Inggris di Sekolah Menengah Atas - Uray Siti Annisa Ravi Ardha; Ikhsanudin , Ikhsanudin Ikhsanudin; Suhartono, Luwandi; Ikhsanudin, Ikhsanudin; Suhartono, Suhartono (English Education:Journal of English Teaching and Research, 2021)
Analytical exposition text is one of the texts studied by eleventh-grade students, and they are asked to produce the analytical exposition text by themselves. However, they faced some difficulties that impede their teaching and learning of making the analytical exposition text. This research aimed to design Materials of Writing Analytical Exposition Text (MOWAET) as a supplementary teaching material to support teaching and learning analytical exposition text. This research was developmental research and applied ADDIE as the procedure to design the materials. Still, there were only three implemented phases in this research: analyzing, designing, and developing. MOWAET was the completed design product for teaching-learning analytical exposition text. The researcher interviewed an English teacher of SMA Negeri 4 Pontianak to do the analyzing phase. MOWAET was created by using PowerPoint and Animaker as the supporting software. The researcher used an internal evaluation to ensure that the product is usable in the development phase. The internal evaluation phase showed that MOWAET met all the criteria, including the objectives, the content, and the media option. Shortening, it was found that the materials of writing analytical exposition text (MOWAET) are usable to support teaching and learning analytical exposition text.